PENGARUH PERMBERIAN EM4 DAN DOSIS PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) - Nuryatin, Nuryatin; Anshar, Muhammad; Lasmini, Sri Anjar (AGROTEKBIS, 2018)
Lettuce (Lactuca sativa L.) is commonly grown in cold and tropical regions. Lettuce isa seasonal plant consisting of large amount of water. This study used a Randomized Block design (RBD) in a two-factorial experiment. The EM4 was applied at two rates i.e. without EM4 (control, e0) and 5 ml/l.  The chicken manure were added at four differen rates i.e. without manure (control, p0), 5 t/ha (p1), 10 t/ha (p2) and 15 t/ha (p3).  The variables observed were plant height, leaf number, plant and root fresh weight, and plant and root dried weight and leaf area. Highest plant height, largest leaf area, largest root fresh and dried weights were found in the e0 p2 treatment.